2010
DOI: 10.1080/17513750903484321
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of two generic predator–prey models

Abstract: We present the analysis of two reaction-diffusion systems modelling predator-prey interactions, where the predator displays the Holling type II functional response, and in the absence of predators, the prey growth is logistic. The local analysis is based on the application of qualitative theory for ordinary differential equations and dynamical systems, while the global well-posedness depends on invariant sets and differential inequalities. The key result is an L(∞)-stability estimate, which depends on a polyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In the work of Murray [19] and other researchers [18,30,31,32], studies have shown that diffusion contributes in no small measure to stability in a system, it increases the concentrations of lower regions, and decreases concentrations of the higher regions. As a result, pattern formation in the form of nonhomogeneous steady-state and periodic solutions is eminent.…”
Section: Gray-scott Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Murray [19] and other researchers [18,30,31,32], studies have shown that diffusion contributes in no small measure to stability in a system, it increases the concentrations of lower regions, and decreases concentrations of the higher regions. As a result, pattern formation in the form of nonhomogeneous steady-state and periodic solutions is eminent.…”
Section: Gray-scott Systemmentioning
confidence: 99%
“…There will be no diffusion-driven instability. Proof Known that the point (u * , v * ) = (1, 0) is the homogeneous solution for system (31). The matrix J for the Gray-Scott reaction-diffusion system (31) is…”
Section: Gray-scott Systemmentioning
confidence: 99%
“…Remark (Further applications) The analysis can be applied to a large number of problems unrelated to the theory of pattern formation. Garvie and Trenchea [2009] provide an example applicable to ecology and the aforementioned paper of Morgan [1989] contains further examples as well as the numerous citations of said paper that use the approach on various problems.…”
Section: 5mentioning
confidence: 99%
“…Jiang et al in [14] consider a predator-prey model with Beddington-DeAngelis functional response subject to the homogeneous Neumann boundary condition. Moreover, Wang et al [15] investigated the spatial pattern formation of a predator-prey system with prey-dependent functional response of Ivlev type and reaction-diffusion whereas the analysis of predator-prey systems showing the Holling type II functional response is examined in Garvie and Trenchea [16]. Moreover, we can point to other efficient numerical methods for solving the reaction-diffusion equations arising in biology such as [17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%